THE POWER OF MERCY IN BIBLICAL LAW - Welker, Michael (Journal of law and religion, 2014)
Biblical law is a complex concept that contains several distinct legal currents. In an effort to explore the interplay of these currents, this article first focuses on the overlap between the biblical law of God and the strictly legal regulations of the Old Testament. It then unpacks the principles and inner rationalities of what is termed "archaic law" and shows that this law is connected with regulations that could be termed "mercy laws" and with cultic regulations. By extrapolating the normative dynamics between these three codes of the law, the article exposes the enormous moral, religious, and legal influence of biblical law in general and of the mercy code in particular. In this way, the article reveals a backbone of our occidental culture. The interdependence of justice and mercy drives societies and cultures to search for (humane) justice in a deep and truth-bound way and, further, to routinize social care and welfare beyond the boundaries of families and tribal relations. The article finally illuminates both commonalities and differences between mercy and a deep and encompassing understanding of love.